International Relations Reseach at the Semiperiphery: Reflections on the 50th Anniversary of the Journal Mezinárodní vztahy (Czech Journal of International Relations, 2016)
The article considers the 50th anniversary of the journal Mezinárodní vztahy from the perspective of Immanuel Wallerstein’s world-systems theory. It shows how the journal and its establishment and development reflect the structural position of the Czechoslovak/Czech International Relations research at the semiperiphery. The concept of semiperiphery captures both the place of a political community (Czechoslovakia/Czech Republic) in the global world-system and the position of a research community (International Relations) within the global scientific field. The article poses three questions. First, is it possible, despite structural constraints, to produce world class research in the Czech context? Second, are there any advantages stemming from the semiperipheral position? Third, does the Czech research community have an exceptional role to play with regard to any questions and topics? The article argues that it is possible to produce world class research in the Czech Republic because there are some advantages to the semiperipheral position. The Czech research community has a key role to play in shaping social and political debates within the Czech political community.